Rancang Bangun Robot Line Follower berbasis Labview Menggunakan Proportional Integral Derivative (PID) - Muhammad Rizal Taufik (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2015)
Abstract - Line follower is one of the automatic robots that can. The line follower robot uses line sensors as input readers to move the robot, the sensor reads the black line and the white track base. This research aims to be implemented in the State actually, her example robot introduction to food at a restaurant. On line follower robot using 3 pieces of infrared sensors, which serve as a reading of the black lines, 2 motor, which functions as an actuator, 1 piece motor driver L298 who serves as controller and motor, 1 piece Arduino Uno that serves as a processing system of line follower. After doing the research and testing of these systems can work well. The success rate of this system reaches 90%. From a level of success that reaches 90%, there is still a shortage of system on the performance of the sensor, because the light on in the received sensor in each room is different, so the sensor must be calibrated first. It needs a system of control to adjust the balance of the line follower robot, so that it can move with the steady and able to cope with disruptions given as the control balance control used Proportional Integral Derivative (PID) using application Labview. Can be simpulakan that the system can be implemented on actual circumstances.